Recurrent spline-method of estimation spectrum - Білецький, А. Я.; Шелевицький, I. B.; Шутко, В. М. (Proceedings of National Aviation University (archive), 1999)
Offered is the recurrent method of an estimation of spectrum by the method of the smallest squares provided that it is possible to approximate the spectrum by a local spline